Accounting for institutional variation in expected returns to higher education - Dorius, Shawn; Tandberg, David; Cram, Bridgette (Education Policy Analysis Archives, 2017)
This study leverages human capital theory to identify the correlates of expected returns on investment in higher education at the level of institutions. We leverage estimates of average ROI in post-secondary education among more than 400 baccalaureate degree conferring colleges and universities to understand the correlates of a relatively new metric of institutional ROI. Results indicate that a diverse undergraduate student body, high graduation rate, and public university status are strong, positive, and robustly associated with institutional ROI. The model accounts for more than 70% of inter-university variation in ROI, suggesting that the factors we have identified are among the most important correlates of institutional ROI. We discuss the policy implications of these findings for institutions of higher education in the context of institutional rankings and a rapidly evolving education landscape, giving special attention to student body characteristics colleges and universities.